MONITORING OF OIL ANALYSIS THROUGH SENSORS - Magalhães Viegas Junior, Daniel (Journal of Interdisciplinary Debates, 2024)
Inserting the Industry 4.0 universe into companies is necessary to guarantee their competitiveness and continuity in the market. And, one of the areas in which industry 4.0 and its technologies are most prominent is maintenance, as the use of intelligent mechanisms are capable of promoting the reliability of systems functioning, predicting failures and anticipating problems and breakdowns in equipment. , thus contributing to increased performance and reduced aggregate costs. The present study then starts from the idea of using Lab-on-chip technology for the hydraulic fluid and lubricant monitoring system and aims to verify the application of Microelectromechanical Systems (MEMS) in maintenance. From the literary review, it was possible to verify that studies relating the use of microsensors for monitoring lubricants are still scarce and from this, applied research was suggested for this purpose, developing a lab-on-chip that be capable of replacing complex and high-cost laboratory analyses.